Assessing the relevance of the applied bachelor's curriculum in culinary arts to industry competency needs: A needs assessment study - Fajar Nur Cahyani; Prihastuti Ekawatiningsih; Kurni Marifa; Rika Nuryani Suwarno (Jurnal Pendidikan Vokasi, 2026)
Rapid changes in the culinary industry require vocational higher education institutions to continuously align their curricula with evolving industry competency needs. However, few studies have comprehensively evaluated curriculum alignment in Applied Bachelor Culinary Arts programs by integrating industry competency requirements, future workforce challenges, and normative gap analysis. Therefore, this study aimed to assess curriculum alignment and identify priorities for curriculum improvement. This study employed a needs assessment approach using a descriptive quantitative design supported by qualitative interviews. Data were collected from 50 industry stakeholders and complemented by interviews with 20 lecturers and industry representatives. The questionnaire consisted of 12 items across three dimensions: Graduate Competencies, Curriculum Relevance, and Future Challenges. Content validity was established through expert judgment, with Aiken’s V values ranging from 0.833 to 0.917. Data were analyzed using descriptive statistics, ranking analysis, interpretation criteria, and normative gap analysis. The findings indicate that the curriculum is generally well aligned with industry needs. The Future Challenges dimension achieved the highest mean score (M = 4.55; Gap = 0.46), followed by Curriculum Relevance (M = 4.23; Gap = 0.78), whereas Graduate Competencies showed the largest gap (M = 3.97; Gap = 1.03). Among the indicators, industry-relevant learning materials received the highest rating (M = 4.76), while the balance between theory and practice (M = 3.32) and the development of soft skills (M = 3.38) received the lowest ratings. These findings provide empirical evidence to guide curriculum developers in strengthening workplace learning, industry collaboration, digital competencies, entrepreneurship, and the integration of Industry 4.0 principles, thereby enhancing graduate readiness for the evolving culinary workforce.